The Incredibles [videorecording (Blu-Ray + DVD)] - Giacchino, Michael (Disney Blu-ray., 2019)
Bob was one of the world's greatest superheroes fifteen years ago; now he's an insurance adjuster, living in the suburbs. Wanting to get back into action, he gets his chance when a mysterious call summons him to an island for a top-secret assignment.